Governing heatwaves in Europe: comparing health policy and practices to better understand roles, responsibilities and collaboration - Kirsten Vanderplanken; Peter van den Hazel; Michael Marx; Ahmad Zia Shams; Debarati Guha-Sapir; Joris Adriaan Frank van Loenhout (Health Research Policy and Systems, 2021)
Abstract Background The expectation that climate change will further exacerbate extreme weather events such as heatwaves is of primary concern to policymakers and scientists. Effective governance is fundamental to preparedness for and response to such threats. This paper explores the governance structures of European heat health action plans and provides insights into key stakeholders, roles, responsibilities and collaboration. Methods This was a two-phase qualitative study, in which we complemented a desk review of 15 European national heat health action plans (NHHAPs) with, after obtaining informed consent, 68 interviews in nine countries with key informants involved in the development, implementation and/or evaluation of these NHHAPs. A thematic analysis was used to analyze the NHHAPs inductively. This analysis focused on three themes: identifying key stakeholders, defining and assigning roles and collaboration among stakeholders. The iteratively created codebook was then applied to the analysis of the key informant interviews. All analyses were done using NVivo 10 qualitative analysis software. Results The majority of the NHHAPs have governance as one of their main objectives, to support the coordination of actions and collaboration among involved stakeholders. There are, however, significant differences between plan and practice. On the basis of the available data, we have little insight into the process of stakeholder identification, but we do find that most countries involve the same types of stakeholders. Roles are mainly defined and assigned in relation to the alert levels of the warning system, causing other role aspects and other roles to be vague and ambiguous. Collaboration is key to many NHHAP elements and is mainly experienced positively, though improvements and new collaborations are considered. Conclusions Our findings show a need for a more deliberate and structured approach to governance in the context of NHHAPs. A cross-sectoral approach to the identification of key stakeholders can facilitate a broader preparedness and response to heatwaves. Roles and responsibilities of stakeholders should be defined and assigned more clearly to avoid confusion and to improve effective implementation. To this extent, we identify and describe seven key roles and potential stakeholders to which these roles are usually assigned. Finally, also collaboration among stakeholders can benefit from a cross-sectoral approach, but also formal structures can be beneficial.